ABCB1 c.-6-180T > G polymorphism and clinical risk factors in a multi-breed cohort of dogs with refractory idiopathic epilepsy. (November 2019) - Gagliardo, T.; Gandini, G.; Gallucci, A.; Menchetti, M.; Bianchi, E.; Turba, M.E.; Cauduro, A.; Corlazzoli, D.S.; Gianni, S.; Baroni, M.; Bernardini, M.; Gentilini, F.
Highlights: ABCB1 c.-6-180T > G polymorphism has been found in several canine breeds with idiopathic epilepsy, besides Border collies. The ABCB1 c.-6-180G allele was not significantly correlated with refractory idiopathic epilepsy in a multi-breed population. The effect of the ABCB1 c.-6-180T > G polymorphism is likely modulated by genetic backgrounds of the various breeds. Cluster seizures represent the main clinical risk factor for refractoriness. Abstract: Epilepsy is the most common chronic neurological disorder in dogs. Approximately 20–30% of dogs do not achieve satisfactory seizure control with two or more anti-epileptic drugs at appropriate dosages. This condition, defined as refractory epilepsy, is a multifactorial condition involving both acquired and genetic factors. The P glycoprotein might play and important role in the pathophysiological mechanism and it is encoded by the ABCB1 gene. An association between a single nucleotide variation of the ABCB1 gene (c.-6-180T > G) and phenobarbital resistance has previously been reported in a Border collie population with idiopathic epilepsy. To date, the presence and relevance of this polymorphism has not been assessed in other breeds. A multicentre retrospective, case-control study was conducted to investigate associations between ABCB1 c.-6-180T > G, clinical variables, and refractoriness in a multi-breed population of dogs with refractory idiopathic epilepsy. A secondary aim was to evaluate the possible involvement of the ABCB1 c.-6-180 T > G single nucleotide variation this population. Fifty-two refractory and 50 responsive dogs with idiopathic epilepsy were enrolled. Of these, 45 refractory and 50 responsive (control) dogs were genotyped. The G allele was found in several breeds, but there was no evidence of association with refractoriness ( P = 0.69). The uncertain role of the c.-6-180T > G variation was further suggested by an association between the T/T genotype with both refractoriness and responsiveness in different breeds. Furthermore, high seizure density (cluster seizure) was the main clinical risk factor for refractory idiopathic epilepsy ( P = 0.003).